Manajemen Pemasaran dalam Peningkatan Penerimaan Peserta Didik di SDII Luqman Al-Hakim Batam - Enik Nur Fa’izah (CV. ULIL ALBAB CORP, 2022)
Marketing becomes something that must be implemented by the school, in addition to being intended to introduce, marketing in educational institutions serves to form a good image of the institution and attract the interest of a number of prospective students. This research is qualitative research with the subject and object of research, namely the principal of SDII Luqman Al Hakim Batam. Sampling using purposive sampling technique. Data collection using observation techniques, interview techniques and documentation techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The result of this study is marketing management in improving the acceptance of students in sdii luqman al-hakim Batam through several stages,, namely planning,, organizing,, implementation and evaluation.